PENINGKATAN KESEJAHTERAAN PETANI MELALUI SISTEM EKONOMI BERBASIS AGROINDUSTRI MODERN - Rita Hayati; Yukimam Armadi; Al-Amin (JOURNAL OF COMMUNITY DEDICATION, 2025)
The purpose of this study is to find out how the process of Improving Farmers' Welfare through the Modern Agroindustry-Based Economic System. The form of this research is descriptive, analytical, and critical. Therefore, the author can comprehensively describe how to Improve Farmers' Welfare through the Modern Agroindustry-Based Economic System. In this study, the authors optimally use two data sources related to this study, namely. Primary data sources and secondary data sources. The main sources of this research are books and scientific journals on Improving Farmers' Welfare through. At the same time, this research is supported (secondary), namely the Modern Agro-Industry-Based Economic System. The result of this research is that the modern agro-industry-based economic system is a strategic solution to improve the welfare of farmers. With the integration of technology, agricultural product processing, and digitalization, farmers can obtain higher added value and have wider market access. Therefore, support from the government, the private sector, and the active participation of farmers are needed to realize a sustainable agro-industrial system.